Enhancing political participation in democracies: what is the role of social capital - Krishna, Anirudh (2002)
What factors account for a more active and politically engaged citizenry? Macro-national institutions, micro-level influences (such as individuals' wealth and education), and meso-level factors, particularly social capital, have been stressed variously in different studies. How do these different factors stack up against one another? What contribution does social capital make compared with the other factors? And how - through what channels - is social capital brought to bear on issues of democratic participation? These questions are examined here with the help of an original data set collected over 2 years for 69 village communities in two north Indian states, including interviews with more than 2,000 individual respondents. Analysis reveals that institutions and social capital work together in support of active participation. Social capital matters, and its effects are magnified when capable agents are also available who can help individuals and communities connect with public decision-making processes. Reproduced.
Keywords: Political participation